How Does AI Enable Rapid Diagnostic Testing in Emergencies? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
In the high-stakes environment of emergency medicine, timely and accurate diagnosis is critical. However, the chaotic nature of emergency departments (EDs), ...
Keywords: AI in Emergency Medicine; Enable; Rapid; Diagnostic; Artificial Intelligence; Healthcare; Clinical Decision Support